Defensive Functioning of Individuals Diagnosed With Gender Dysphoria at the Beginning of Their Hormonal Treatment - Giovanardi, Guido; Mirabella, Marta; Di Giuseppe, Mariagrazia; Lombardo, Francesco; Speranza, Anna Maria; Lingiardi, Vittorio (Frontiers in Psychology, 2021)
Defense mechanisms are relevant indicators of psychological functioning and vulnerability to psychopathology. Their evaluation can unveil individuals’ unconscious strategies for mediating reactions to emotional conflict and external stressors. At the beginning of their journey towards gender reassignment, individuals diagnosed with gender dysphoria (GD) may experience conflict and stressful experiences that trigger a wide range of defense mechanisms. Mature defenses may strengthen these individuals as they travel along this important path, while neurotic and immature defenses may exacerbate their body dissatisfaction and hinder their processing of change. Only a few studies have investigated self-reported defensive functioning in transgender people, finding a higher frequency of maladaptive defense mechanisms relative to controls. The present study was the first to apply an in-depth clinician-rated tool to assess the entire hierarchy of defense mechanisms within a sample of transgender people. Defensive functioning and personality organization were assessed in 36 individuals diagnosed with GD (14 trans women, 22 trans men, mean age 23.47 years), using the Defense Mechanisms Rating Scales (Perry, 1990) and the Shedler-Westen Assessment Procedure-200 (Shedler et al., 2014). Body uneasiness was assessed using the Body Uneasiness Test (BUT; Cuzzolaro et al., 1999). The findings showed that defensive functioning correlated positively with healthy personality functioning and negatively with body dissatisfaction. Compared to cisgender controls, participants with GD who presented greater defensive functioning were found to be more immature and to demonstrate significant differences in many levels of functioning. The clinical implications of the results suggest that psychological interventions aimed at improving defensive functioning in individuals with GD will be important in helping them manage the challenges posed by their gender transition.